Condition Of Coral Reef Cover in Bungkaih Waters, Muara Batu District, North Aceh Regency, Aceh Province - Imanullah Imanullah; Erlangga Erlangga; Cut Meurah Nurul Akla; Intan Mutia (Fakultas Perikanan dan Kelautan, Universitas Riau, 2022)
This research aims to know the percentage of life coral reef cover and death coral reef cover and knowing condition of coral reef cover In Bungkaih Waters, Muara Batu District, North Aceh Regency, Aceh Province. This research was carried out in August 2021. Data collection was carried out at two stations in Bungkaih waters, each station depth 3 and 6 m. Station determined was carried with purposive sampling method base on condition coral reef cover, to know condition of coral reef cover in this research used Point Intercept Transect (PIT) method that 25 m long using marked ropes every 0,5 m or roll meter scale base on Manuputty & Djuwariah (2009). Base on observation life coral reef cover at each station is Acropora, Non-Acropora and Soft Coral. Station I percentage of coral reef cover is 14,12 % belong to category bad, station II percentage of coral reef cover is 45,08 % belong to category medium. Observation result death coral reef cover at each stations Death Coral Reef Algae higher than percentage coral reef anymore. Station I and II percentage death coral reef cover (Death Coral Algae) is 85,88 % and 54,35 %.